Forest fortitude - Yu, Bill (Survive! (Graphic Planet (Firm)), 2020)
Jason arrives at Camp Elphick intent on letting everyone know he is a gamer and not interested in the woods. Then he and his safety partner fall in a river attempting a selfie and end up lost in the woods. Includes true survival stories, a forest survival guide, critical thinking question, trivia, and a glossary.